Monitoring CD27 Expression to Evaluate Mycobacterium Tuberculosis Activity in HIV-1 Infected Individuals In Vivo - Schuetz, Alexandra (Public Library of Science, 2011)
The level of bacterial activity is only poorly defined during asymptomatic Mycobacterium tuberculosis (MTB) infection. The objective was to study the capacity of a new biomarker, the expression of the T cell maturation marker CD27 on MTB-specific CD4 T cells, to identify active tuberculosis (TB) disease in subjects from a MTB and HIV endemic region. The frequency and CD27 expression of circulating MTB-specific CD4 T cells was determined in 96 study participants after stimulation with purified protein derivative (PPD) using intracellular cytokine staining for IFNgamma (IFNγ). Subjects were then stratified by their TB and HIV status. Within PPD responders, a CD27(−) phenotype was associated with active TB in HIV(−) (p = 0.0003) and HIV(+) (p = 0.057) subjects, respectively. In addition, loss of CD27 expression preceded development of active TB in one HIV seroconverter. Interestingly, in contrast to HIV(−) subjects, MTB-specific CD4 T cell populations from HIV(+) TB-asymptomatic subjects were often dominated by CD27(−) cells. These data indicate that down-regulation of CD27 on MTB-specific CD4 T cell could be used as a biomarker of active TB, potentially preceding clinical TB disease. Furthermore, these data are consistent with the hypothesis that late, chronic HIV infection is frequently associated with increased mycobacterial activity in vivo. The analysis of T cell maturation and activation markers might thus be a useful tool to monitor TB disease progression.